Аэроупругое взаимодействие лопаточных венцов в пятиступенчатом осевом компрессоре в трехмерном потоке идеального газа - Гнесин, Виталий Исаевич; Колодяжная, Любовь Владимировна (НТУ "ХПИ", 2011)
The numerical results for aeroelastic interaction of the blade rows of five stage axial compressor in 3D ideal gas flow have bee npresented. There shown that the principal contribution in unsteady loads is brought by the harmonics with frequencies which are equal to the product of rotation frequency on the stator blades numbers, but principal contribution in blades oscillationsis brought by autooscillations with frequency closed to the first natural frequency.
Keywords: колебание лопаток; трансзвуковой поток; осевые зазоры; декартовая система координат; аэродинамические нагрузки